3D reliability evaluation of tunnels under strong-motion earthquakes considering spatial randomness. Issue 7 (3rd July 2017) - Yue, Qingxia; Ang, Alfred H.-S.
Abstract: This paper studied the stochastic response and reliability of the tunnel system through modelling the elastic modulus and yield stress of the surrounding soil as a random field. A 3D tunnel-soil finite element model was established and the corresponding random field was simulated by the spectral representation method. The Wenchuan earthquake was chosen as input from the bottom in the perpendicular direction to the longitudinal axis. Results show that the peak values of the internal forces of the cross sections of the tunnel are not uniformly distributed and the hoop forces and bending moments are higher under the condition that the elastic modulus and yield stress of soil are both random fields (Case II) than only the elastic modulus of the soil is considered as random field (Case I). Using PDEM (probability density evolution method), the stochastic response of the tunnel indicates that the probability density function of the response is complex with two or more peaks. The design limit and ultimate limit states of Cases I and II are evaluated in this paper in terms of the respective reliabilities, which indicated that the reliability under Case II is lower than that of Case I.